2007
DOI: 10.1007/s00213-006-0663-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the potency of κ opioids and mixed-action opioids administered systemically and at the site of inflammation against capsaicin-induced hyperalgesia in rats

Abstract: These findings demonstrate sex differences in kappa opioid activity in a persistent pain model. Although an NMDA antagonist blocked the effects of kappa opioids in this model, these effects were not sexually dimorphic as reported in most acute pain models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
3
17
1
Order By: Relevance
“…In the present study, the mu agonists nalbuphine, morphine, and methadone all produced dose-dependent decreases in rates of schedule-controlled responding and increases in thermal antinociception consistent with previously published studies (Dykstra and Woods, 1986;Gerak et al, 1994;Gatch et al, 1995Gatch et al, , 1998Stevenson et al, 2003). This is the first study to describe the antiallodynic effects of nalbuphine in nonhuman primates, although nalbuphine was shown to be effective in some rat models of inflammatory pain (Lomas et al, 2007;Ortiz et al, 2007;Ortiz and Castañ eda-Herná ndez, 2008). Clomipramine produced little or no effect up to the highest dose tested in all three assays, which agrees with previous studies in finding that clomipramine and other serotonin uptake inhibitors produce little effect on rates of schedule-controlled responding or thermal nociception in nonhuman primates (Kleven and Woolverton, 1993;Spealman, 1993;Gatch et al, 1998) or pain-related behaviors in rodent models of inflammatory pain (Pedersen et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the mu agonists nalbuphine, morphine, and methadone all produced dose-dependent decreases in rates of schedule-controlled responding and increases in thermal antinociception consistent with previously published studies (Dykstra and Woods, 1986;Gerak et al, 1994;Gatch et al, 1995Gatch et al, , 1998Stevenson et al, 2003). This is the first study to describe the antiallodynic effects of nalbuphine in nonhuman primates, although nalbuphine was shown to be effective in some rat models of inflammatory pain (Lomas et al, 2007;Ortiz et al, 2007;Ortiz and Castañ eda-Herná ndez, 2008). Clomipramine produced little or no effect up to the highest dose tested in all three assays, which agrees with previous studies in finding that clomipramine and other serotonin uptake inhibitors produce little effect on rates of schedule-controlled responding or thermal nociception in nonhuman primates (Kleven and Woolverton, 1993;Spealman, 1993;Gatch et al, 1998) or pain-related behaviors in rodent models of inflammatory pain (Pedersen et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…The drugs [D-Ala 2 , N-Me-Phe 4 , Gly 5 -ol]-Enkephalin acetate salt (1) (DAMGO, 5 µg/paw); [D-Pen 2,5 , p-Cl-Phe 4 ]-Enkephalin (DPDPE, 20 µg/paw); (−)- trans -(1S,2S)-U-50488 hydrochloride hydrate (U 50,488, 10 µg/paw) [23]; Prostaglandin E 2 (PGE 2 , 100 ng/paw) [23], [24]; D-Phe-Cys-Tyr-D-Trp-Orn-Thr-Pen-Thr amide (CTOP, 20 µg/paw) [25], [26], nor-binaltorphimine dihydrochloride (nor-BNI, 50 µg/paw) [25], [27]; N,N-diallyl-Tyr-Aib-Aib-Phe-Leu (ICI 174,864, 10 µg/paw) [25], methiodide naloxone (1 mg/Kg, subcutaneously) were used in this study [28]. These drugs were purchased from Sigma-Aldrich, Saint Louis, MO, USA.…”
Section: Methodsmentioning
confidence: 99%
“…However, this should not be interpreted to mean that μ opioid receptor agonists are antinociceptive in males and κ opioid receptor agonists are antinociceptive in females. Two recent studies51,52 examined κ receptor agonists in rats and mice and found that males had a greater response than females. This response contradicts earlier work17,47–49 and is similar to the antinociceptive response of rodents to μ receptor agonists.…”
Section: Animal Modelsmentioning
confidence: 99%